Implementation of Weekly English Program with Fun Learning Method for Pesantren Students - Muhammad Iksan; Husnaini Husnaini; Marsruddin Masruddin (Universitas Cokroaminoto Palopo, 2022)
Community development requires support from various parties, both from the government, academics and community members. The Morowali Regency Government has one program, namely to make Islamic Boarding School institutions as an educational forum that will prepare better human resources in Morowali Regency. To achieve this goal, the government has provided funds for physical development and human resources for every pesantren in the district. Nurul Ummah Lambelu Islamic Boarding School, Bumi Raya Sub District Morowali Regency conducts mentoring activities for teachers to support Morowali Regency government programs. This article was focused on implementation and the impact of the weekly English program in which English teachers at Pesantren were given training and assisted in implementing the weekly English program. This program is carried out collaboratively between lecturers and students of the English Education Study Program IAIN Palopo. The aim of the activity is to improve human resources and the competitiveness of the people of Morowali Regency in facing the conditions as a large industrial center in Indonesia through mastery of foreign languages with Fun Learning Method. The method used is descriptive qualitative research method.. The instruments used are observation and interviews. Qualitative descriptive is done through observation and interviews. The result show that this weekly English Program with Fun Learning Method is very helpful for teacher and of course it can support the English of pesantren’s students. The implementation of Fun Learning can support and motivate the students at Pesantren in Learning English.